2011
DOI: 10.1016/j.juro.2011.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Alexander Technique on Improving Posture and Surgical Ergonomics During Minimally Invasive Surgery: Pilot Study

Abstract: The Alexander technique training program resulted in a significant improvement in posture. Improved surgical ergonomics, endurance and posture decrease surgical fatigue and the incidence of repetitive stress injuries to laparoscopic surgeons. Further studies of the influence of the Alexander technique on surgical posture, minimally invasive surgery ergonomics and open surgical techniques are warranted to explore and validate the benefits for surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Compared with baseline, significant improvement was observed in post-intervention postural endurance, as assessed by the time-load test (p < 0.05). Tests of surgical skills also showed significant improvements, and tremor in the non-dominant hand was reduced compared with baseline (p < 0.05) (30).…”
Section: Posture and Surgical Ergonomic Skillsmentioning
confidence: 86%
See 2 more Smart Citations
“…Compared with baseline, significant improvement was observed in post-intervention postural endurance, as assessed by the time-load test (p < 0.05). Tests of surgical skills also showed significant improvements, and tremor in the non-dominant hand was reduced compared with baseline (p < 0.05) (30).…”
Section: Posture and Surgical Ergonomic Skillsmentioning
confidence: 86%
“…continued monitoring, painkillers, referral for physiotherapy or surgery, as appropriate); (ii) usual care plus therapeutic massage (one session per week for 6 weeks); (iii) usual care plus six one-to-one AT lessons (Table 1); (iv) usual care plus 24 one-to-one AT lessons (Table 1); (v) to (viii) as for (i) to (iv) but with an exercise prescription for general aerobic exercise such as walking, backed up by nurse-delivered behavioural counselling (14). Six AT lessons were chosen as being an affordable number from the perspective of the UK National Health Service (NHS), and 24 AT lessons were selected to reflect private practice, where [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] AT lessons are typical for people with back pain. AT lessons were provided by teachers trained by, and registered with, the Society of Teachers of the Alexander Technique (STAT), with at least 3 years' experience.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in positive attitude has been found in response to AT over prescribed exercises (30), which is consistent with the results of the present study. Reddy (37) reported that participants reported greater skill, less pain, and better posture after six 45-minute AT training sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, surgeons' posture has received increasing attention as a major ergonomic challenge during surgical procedures. It has been well documented that improving ergonomic conditions, muscle endurance, and posture during laparoscopic surgeries would decrease the level of fatigue and the inci-dence of repetitive stress injuries among the surgeons (4). While open surgery required the surgeon to utilize conventional surgical tools and operate directly on the patient, minimally invasive surgeries necessitate the use of a variety of techniques and technologies over longer periods of time (3).…”
Section: Introductionmentioning
confidence: 99%